Morphometric analysis and hydrological implications of the Himalayan River Basin, Goriganga, India, using Remote Sensing and GIS techniques - Parvaiz Ahmad Ganie; Ravindra Posti; Garima; Kishor Kunal; Nityanand Pandey; Pramod Kumar Pandey (Journal of Groundwater Science and Engineering)
The application of Geographic Information System (GIS) methodologies offers valuable insights into the hydrological behaviour of watersheds through the analysis of their morphometric attributes. This study focuses on the Goriganga River, a major tributary of the Ganga River system, by conducting a detailed morphometric analysis using Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) imagery with 30 m resolution, alongside survey of India topographic sheets. Thirty-two watersheds within the river basin were delineated to calculate linear, areal, and relief morphometric parameters, covering a total drainage area of 2,183.11 km2. The drainage pattern, primarily dendritic to sub-dendritic, is shaped by the region's topography, geological structure, and precipitation patterns. Classified as a 6th-order basin, the drainage density ranges from 1.21 km/km2 to 1.96 km/km2, underlining the significant influence of the regional physiography and lithological composition on the stream ordering. Relief analysis suggests the basin is in an early developmental stage, characterised by varying slope gradients and a low to moderate risk of soil erosion. The basin's hydrogeology is complex, with aquifer distribution primarily governed by lithological factors. Limestone, due to its high permeability and karst features, forms the principal aquifer, although it is susceptible to contamination. In contrast, groundwater potential in the Basement Gneissic Complex and Schist regions is limited to structurally controlled zones, while shale acts as an aquitard. The basin's heterogeneous aquifer characteristics emphasize the need for localized groundwater management strategies tailored to specific lithological units. The integration of remote sensing and GIS techniques effectively delineates the basin's morphometric and hydrogeological characteristics, providing critical information for the development of sustainable water resource management strategies.